PEMANFAATAN LIMBAH KOTORAN SAPI DAN JERAMI KACANG TANAH SEBAGAI BOKASHI CAIR BAGI PERTUMBUHAN TANAMAN SAWI (Brassica juncea L.) - Artiana Artiana; Lilis Hartati; Abrani Sulaiman; Jamzuri Hadie (EnviroScienteae, 2016)
Has conducted a study entitled " Cow Manure Waste Utilization and Straw Peanut For Liquid Bokashi For Plant Growth mustard (Brassica juncea L.)". This study aimed to analyze the nutrient content in the liquid Bokashi is derived from cow dung and straw peanuts, and study the effect of dosing Bokashi different liquid to the growth of the mustard plant (Brassica juncea L.). Methods using a completely randomized design with one factor at a dose of 125 ml, 250 ml, 375 ml and 500 ml, and as control using Bokashi solid. This research was conducted with four replications. Bokashi liquid nutrient content of C of 0,1045%, 0,0461% of N, P and K amounted to 0.0172% at 0.2500%. The content of nutrient dense Bokashi C of 6,0874%, 2,0169% of N, P and K amounted to 0,0218% at 5,7802%. Bokashi dosing different liquid to the growth of mustard (Brassica juncea L.) significant effect on the growth of mustard, but still lower than the solid Bokashi. Dose liquid Bokashi most optimal for growing mustard (Brassica juncea L.) is at 375 ml.